PARENTAL BACKGROUND AS DETERMINANT OF CAREER CHOICE AMONG STUDENTS OF UNIVERSITY OF PROFESSIONAL STUDIES, ACCRA, GHANA - Bruce, Daniel; Asante, Akua Bema (International Journal of Research -GRANTHAALAYAH, 2024)
The aim of the study was to examine how parental background variables (education, occupation and income) serve as determinants of career choice among the students of the University of Professional Studies, Accra. The simple random technique was used to select 200 respondents for this study. The Parental Variable and Career Choice questionnaires were used in collecting data. Descriptive statistical tests were used in analyzing data with the aid of the Statistical Product and Service Solutions (SPSS) software. Frequency distribution tables, pie chart and bar graph, binomial test, chi square and Mann-Whitney test were used to fulfil the objectives of the study. The results showed that both parental educational and occupational background have influence on the career choice of the students. Parental income however, did not prove to have any influence on career choice. Gender difference was also not found to influence career choice amongst target population. It was concluded that, parental educational and occupational background have an influence on students’ career choice but parental income was not found to determine students’ career choice. It is, therefore, recommended that parents and other stakeholders in career development of students take into consideration influence of parental education and occupation on career development of students and use them in guiding, shaping, educating, and introducing students to surge into the world of career interest exploration and career choice. Students should be encouraged to choose role models whose educational and occupational levels placed them high on good career progression to become their images of inspiration in career choice and preference.